A few of our favorite unconfirmed ideas. (December 2015) - Marini, John; Gattinoni, Luciano; Ince, Can; Kozek-Langenecker, Sibylle; Mehta, Ravindra; Pichard, Claude; Westphal, Martin; Wischmeyer, Paul; Vincent, Jean-Louis
Abstract Medical practice is rooted in our dependence on the best available evidence from incremental scientific experimentation and rigorous clinical trials. Progress toward determining the true worth of ongoing practice or suggested innovations can be glacially slow when we insist on following the stepwise scientific pathway, and a prevailing but imperfect paradigm often proves difficult to challenge. Yet most experienced clinicians and clinical scientists harbor strong thoughts about how care could or should be improved, even if the existing evidence base is thin or lacking. One of our Future of Critical Care Medicine conference sessions encouraged sharing of novel ideas, each presented with what the speaker considers a defensible rationale. Our intent was to stimulate insightful thinking and free interchange, and perhaps to point in new directions toward lines of innovative theory and improved care of the critically ill. In what follows, a brief background outlines the rationale for each novel and deliberately provocative unconfirmed idea endorsed by the presenter.